Covenants and Courtrooms, Imputation and Imitation Righteousness and Justification in "Paul and the Faithfulness of God" - Starling, David Ian; Wright, N. T. 1948- (2014)
This article offers a response to the discussion of righteousness and justification in N. T. Wright's Paul and the Faithfulness of God. Though finding much in Wright's treatment to appreciate, it argues for a greater emphasis on the active, ethical dimensions of what Paul has in mind by "righteousness" (divine and human) and for the retention of the notion of the imputation of Christ's righteousness to believers, not as an explicit Pauline assertion but as a legitimate inference from Pauline premises. Understood in this manner, the doctrine of imputation (far from cutting the nerve between justification and transformation) opens up a way to draw straighter, clearer lines of commensurability and correspondence between the righteousness of God (expressed in his actions as creator, covenant maker, law giver, covenant keeper and judge), the righteousness of Christ (imputed to us in our justification and given as an example to imitate), and the righteousness of life to which we are called in the gospel.
Keywords: N. T. Wright; Paul; Pauline Theology; Justification; Righteousness; Ethics; Imputation; Covenant; Rezension